DAMPAK PROGRAM PENGEMBANGAN USAHA AGRIBISNIS PERDESAAN TERHADAP PENDAPATAN ANGGOTA GABUNGAN KELOMPOK TANI (Studi kasus: Desa Banyukuning, Kecamatan Bandungan, Kabupaten Semarang) - Haryo Setiaji; Waridin Waridin (Diponegoro Journal of Economics, 2014)
ABSTRACTBandungan is producing agricultural products with the most comodity varieties compared with other areas in district of Semarang. Banyukuning is one of the village in the district that have received and run the PUAP program (Rural Agribusiness Program), and owned the largest population of farmers, specifically for chilli farmers. PUAP program in Banyukuning managed and run by Farmers Group Association (Gapoktan) Guyub Makmur for revolving capital loan for its members. This study aims to determine how the PUAP program progresses and knowing its impact on farmers' income. Data collection methods in this study is using direct interviews to the relevant parties and questionnaires. While data analysis method is using the Paired t-test and using the R / C ratio on the chilli hybrid farming after receiving PUAP capital loans This study results showed all respondents used PUAP to increase their capital. The funds are used to purchase seeds and fertilizers. Testing distinction statatistik R / C ratio of before and after PUAP indicate its value t worth -17,649 with significance of 0,000 < 0.05.  This means that there is a significant difference of R / C ratio on before and after PUAP where after puap R / C ratio PUAP greater than before.